2021
DOI: 10.1200/jco.2020.39.28_suppl.113
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating health disparities in access to genomic testing for metastatic non-small cell lung cancer patients.

Abstract: 113 Background: Over the past decade, genomic testing has become standard of care for metastatic non-small cell lung cancer (NSCLC). These tests qualify patients for additional anti-cancer therapies and should be performed in all patients. Small scale studies at the institutional level have revealed that there may be disparities in genomic testing in NSCLC and not all patients may have similar access to care. In this study, we use the IBM Explorys Electronic Health Record (EHR) database to conduct a nationwid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Health disparities exist in genomic testing in patients with NSCLC. A large study by Yoon et al 30 showed that male, White patients were more likely to receive genomic testing. Another study from Massachusetts General Hospital showed that low-income status and older age were associated with lower rates of genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Health disparities exist in genomic testing in patients with NSCLC. A large study by Yoon et al 30 showed that male, White patients were more likely to receive genomic testing. Another study from Massachusetts General Hospital showed that low-income status and older age were associated with lower rates of genetic testing.…”
Section: Discussionmentioning
confidence: 99%